ASSESSMENT OF PULMONARY INVOLVEMENT IN PATIENTS WITH RHEUMATOID ARTHRITIS BY USING HIGH RESOLUTION COMPUTERIZED TOMOGRAPHY AND PULMONARY FUNCTION TESTING - Necip Güder; Mehmet Ünlü; Nurhan Doğan (Archives of Rheumatology, 2002)
In our study, we aimed to search the prevalence of pulmonary involvement in rheumatoid arthritis (RA), and the relation of clinical parameters with these involvement by using high resolution computed tomography (HRCT) of thorax and pulmonary function test (PFT). We also aimed to evaluated the relation between HRCT and PFT findings. For these purposes, 37 patients with RA diagnosed by using American Rheumatism Association (ARA) criteria were included in the study. As a control group 18 patients without any pulmonary system pathology were randomly selected from patients with knee osteoarthritis. RA group and control group were evaluated by using HRCT and PFT. In addition, RA patients were compared within the group for treatment modalities, disease activity parameters and clinical parameters to evaluate if there is any relation between these parameters and pulmonary involvement. As a result, pulmonary pathologies were diagnosed, using HRCT, frequently in RA patients as 56,8%. High resolution computed tomography showed a range of abnormalities among patients thought to have interstitial lung disease. Interstitial septal thickening was found in 3 patients. Ground glass opacification was present in five, while basal honey combing was also evident in two patients. Bronchiectasis was identified in two patients. These finding were not clinically significant in most cases, however increasing intensity of these pathologies could impair physiologic functions of lung. Pulmonary function tests were found abnormal in 55.6%. It was observed that there was statistically significant decline in peak expiratory flow rate, forced expiratory volume in one second and forced expiratory volume in one second/ forced expiratory volume (p<0.05). We concluded that; HRCT or PFT were not found adequate techniques by themselves for the evaluation of pulmonary system. High resolution computed tomography, in comparison to PFT is not fully adequate to clarify small airway involvement.